Şanlıurfa 2. Organize Sanayi Bölgesindeki Bir Prefabrik Yapının Göçme Nedenlerinin Araştırılması - Pekgökgöz, Recep Kadir; Avcil, Fatih (Fırat University, 2017)
Şanlıurfa 2. Organize Sanayi Bölgesi’nde yer alan ve içerisinde prefabrik elemanların üretiminin yapıldığı bir prefabrik sanayi işletmesinin çatısı çökmüştür. Bu çökme sonucu can ve mal kaybı yaşanmıştır. Bu çalışmada prefabrik yapıda göçmeye neden olan muhtemel sebepler araştırılmıştır. İlk inceleme sonucunda yapının projesine göre tamamlanmadığı ve ağır bir imalat için yoğun bir şekilde kullanıldığı belirlenmiştir. Yapının kullanım süreci içerisinde kren (vinç) ve beton mikserlerinin oluşturduğu dinamik titreşimlerin, özensiz yapılan ve zayıf olan kolon-kiriş bağlantılarında aşırı yanal hareketlere neden olduğu belirlenmiştir. Bunun sonucunda kirişlerden biri bağlantısından kurtularak beş kirişten oluşan çatı sisteminin aşamalı göçme mekanizmasıyla yıkıldığı kuvvetli olarak tahmin edilmektedir. Bu varsayımın doğruluğu, mevcut yapı ve bu yapının tamamlanmış hali sonlu elemanlar yöntemiyle incelenerek test edilmiştir. Mevcut yapı modelinde yer değiştirmelerin tamamlanmış yapı modeline göre oldukça büyük olması mevcut yapının dinamik dış yüklere göre zayıf bir davranış sergilediğini göstermiştir. Elde edilen bu bulgu öngörülen varsayımı doğrulamıştır. Sonuç olarak, prefabrik yapıların projelendirildikleri hallerinden eksik bir durumda inşa edilip kullanılmalarının can ve mal güvenliği bakımından önemli bir risk oluşturduğu anlaşılmıştır

There is a roof collapse at an industrial plant that produces precast structural elements located at Şanlıurfa 2nd Industrial Estate. This collapse resulted in life and economic loss. In this study, possible causes that led to the collapse of this precast building were investigated. The structure has not been completed according to the project and it was determined that load carrying elements of this prefabricated plant intensively used for heavy manufacturing for an external purpose as a result of the first observation. Dynamic vibrations created by the crane and concrete mixers have determined the cause that excessive lateral movement in beam-column connections which is sloppy done and weak in the process of building usable. As a consequence, it is strongly estimated that one of the beams have been left the connection than the roof system consists of five beams have been collapsed by the gradually failure mechanism. The reliability of this assumption was tested by two finite element models. One of them is belong to current status of the in completed prefabricated structure other of them is belong to completed ideal prefabricated structure. Displacement in the current structure model is significantly larger than the complete version of the structure has shown poor behavior exhibits under dynamic external load. The obtained results confirmed the assumptions of this prediction. As a result, the uses of prefabricated buildings that are not in accordance with the project are understood to pose a significant risk in terms of life and property security.
Investigation of the Collapse Reason of a Prefabricated Industrial Plant at Şanlıurfa 2nd Industrial Estate